Effectiveness of Short-Term Use Denosumab and Risedronate Using β-Crosslaps and Histopathology as a Parameter in Osteoporotic Rat Model - Siwendro, Afrisya Bimo; Ramdan, Ahmad; Ismiarto, Yoyos Dias; Yantisetiasti, Anglita; fachri, Dliyauddin (Majalah Kedokteran Bandung, 2024)
Osteoporosis is a condition of decreased bone mass density. Pharmacological management uses drugs that decrease bone resorption or increase bone formation. The most commonly used drugs are bisphosphonates. Risedronate is one of these bisphosphonates. It inhibits osteoclasts, resulting in osteoclast apoptosis. Denosumab is a human monoclonal antibody that inhibits receptor activator kappa-B ligand, inhibiting osteoclast activation. Both drugs are widely used. Research on the efficacy of these two mechanisms has yet to obtain conclusive results. β-cross-laps is a parameter that can be used to evaluate the effectiveness of therapy through monitoring the bone resorption process. This experimental study used female rats >9 weeks old and was conducted at the Pharmacology and Therapeutic Laboratory, Universitas Padjadjaran Bandung, Indonesia, from  June to September 2021. This study utilized a simple random sampling to allocate 24 experimental animals into three groups: control, risedronate, and denosumab. β-Crosslaps expression values before ovariectomy, post ovariectomy before receiving medication, and post ovariectomy and receiving medication was recorded and statistically analyzed using the SPSS version 24.0. The analysis of 24 samples revealed a statistically significant decrease in the median value of β-Crosslaps after ovariectomy in the denosumab group (p=0.036) when compared to the control group, whereas the decrease in the risedronate group was not significant (p=0.687). Administration of denosumab in rat models is more effective in reducing bone resorption compared to risedronate.